2017
DOI: 10.1016/j.amjmed.2017.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Time to Clinically Relevant Fracture Risk Scores in Postmenopausal Women

Abstract: Background Clinical practice guidelines recommend use of fracture risk scores for screening and pharmacologic treatment decisions. The timing of occurrence of treatment-level (according to 2014 National Osteoporosis Foundation guidelines) or screening-level (according to 2011 US Preventive Services Task Force guidelines) fracture risk scores has not been estimated in postmenopausal women. Methods We conducted a retrospective competing risk analysis of new occurrence of treatment-level and screening-level fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 22 publications
(32 reference statements)
0
8
0
Order By: Relevance
“…The choice of 10% for transition to the treatment threshold was selected based on similar previous analyses. 11,12 Separate analyses were conducted for the 3 different treatment strategies described previously. In sensitivity analyses, time for 5%, 20%, or 50% of the population to reach the treatment threshold was modeled, and change in the number of FRAX clinical risk factors was substratified as an increase of 1 vs 2 or more.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The choice of 10% for transition to the treatment threshold was selected based on similar previous analyses. 11,12 Separate analyses were conducted for the 3 different treatment strategies described previously. In sensitivity analyses, time for 5%, 20%, or 50% of the population to reach the treatment threshold was modeled, and change in the number of FRAX clinical risk factors was substratified as an increase of 1 vs 2 or more.…”
Section: Discussionmentioning
confidence: 99%
“…A subsequent study extended these observations to examine the time for 10% of women to develop a treatment-level fracture risk score using US National Osteoporosis Foundation guidelines. 12 Before age 65 years, postmenopausal women with a subthreshold fracture risk score at baseline rarely developed a treatment-level FRAX score. Time to a treatment-level score ranged from 7.6 years (ages 65-69 years) to 5.1 years (ages 75-79 years).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Dual X-ray absorptiometry is based on the quantification of axial bone mineral density (spine and hip) by measuring the transmission of a beam of X-ray photons with two energy peaks in the patient’s body, which allows for the assessment of the calcium content of the bone [ 76 ]. A study conducted in postmenopausal women showed that BMD and fracture risk were related, thus defining osteoporosis as a t-score value of −2.5 [ 77 ].…”
Section: Diagnosis Of Osteoporosis and Fracture Risk Assessmentmentioning
confidence: 99%